2004
DOI: 10.1007/s00702-004-0154-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on homocysteine plasma levels in Alzheimer?s patients. Relevance for neurodegeneration

Abstract: Homocysteine (HC) may work inter alia as a Volume Transmission signal since HC is present in the brain and cerebrospinal fluid and binds to NMDA receptors. Furthermore, in cell cultures increased HC formation increases its export. In the present study we have shown that after intravenous injection in intact animals HC penetrates the blood-brain barrier. Hence, it works as a blood-born humoral signal. Furthermore, we have studied HC plasma levels in a group of Alzheimer's (AD) patients and compared with a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Amyloidosis is accelerated in a mouse model of Alzheimer;s disease (Tg2576 mice) when they are fed a HHcy diet (low folate, vitamin B 6 , and vitamin B 12 ) (185). Hcy is a major risk factor for dementia (4,8,26,49,102,111,141,165). Even mildly elevated Hcy (Ͼ14 mol/l) creates a twofold increase in the risk of dementia with a significant correlation between [Hcy] and cognitive impairment (47,141).…”
Section: Neurological and Neurovascular Disorders In Cbs Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Amyloidosis is accelerated in a mouse model of Alzheimer;s disease (Tg2576 mice) when they are fed a HHcy diet (low folate, vitamin B 6 , and vitamin B 12 ) (185). Hcy is a major risk factor for dementia (4,8,26,49,102,111,141,165). Even mildly elevated Hcy (Ͼ14 mol/l) creates a twofold increase in the risk of dementia with a significant correlation between [Hcy] and cognitive impairment (47,141).…”
Section: Neurological and Neurovascular Disorders In Cbs Deficiencymentioning
confidence: 99%
“…Hcy has two fates in mammals: remethylation to methionine or transsulfuration to cysteine. The elevation of Hcy levels in plasma, hyperhomocysteinemia (HHcy), is an independent and graded risk factor for both cardiovascular (CVD) (61a, 166) and neurovascular (NVD) diseases (4,58,61,86,92,102,131,138,153,187). HHcy is caused by genetic deficiencies in the enzymes responsible for remethylation or transsulfuration of Hcy, nutritional deficiencies in vitamins serving as cofactors for these enzymes, and transient HHcy by dietary overload of methionine-rich foods (e.g., meats, dairy products, sesame seeds).…”
mentioning
confidence: 99%
“…It was in accordance with previous reports that the expression of apoptosis regulatory proteins, Bax and Bcl-2, would be altered by Hcy (15). It was also suggested that Hcy generates reactive oxygen species, which attacks the polyunsaturated fatty acids of neuronal cell membranes and induces lipid peroxidation in the hippocampus (16). Hcy is a non-protein amino acid, or thiol-containing amino, which is derived from methionine (17).…”
Section: Discussionmentioning
confidence: 99%
“…Hcy is a non-essential sulphur-containing amino acid, produced as a natural consequence of methionine metabolism, and its accumulation in the brains of aged individuals appears to be a strong independent risk factor for dementia and other neurodegenerative diseases [27][28][29]. Hcy treatment of cultured cortical neurons caused apoptosis in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 96%